Effect of the projector augmented wave potentials on the simulation of thermodynamic properties of vanadium - Tingting Zhang (AIP Publishing LLC, 2021)
We report significant differences in high-pressure properties of vanadium at zero temperature and finite temperature when different projector augmented wave (PAW) potentials are used in simulations based on density functional theory. When a PAW potential with only five electrons taken as valence electrons is used, the cold pressures in the high-pressure region are seriously underestimated, and an abnormality occurs in the melting curve of vanadium at about 400 GPa. We show that the reason for these discrepancies lies in the differences in the descriptions of the interatomic force, electron dispersion, and anisotropy of electron bonding obtained from different PAW potentials at high pressure, which lead to striking differences in the mechanical stability of the system. We propose a procedure for selecting PAW potentials suitable for simulations at high temperature and high pressure. Our results provide valuable guidance for future simulations of thermodynamic properties under extreme conditions.